IMPLEMENTASI KERJA SAMA SEKOLAH DENGAN DUNIA USAHA DAN DUNIA INDUSTRI (DUDI) DALAM MENINGKATKAN KOMPETENSI LULUSAN SISWA DI SMK NEGERI 4 KOTA JAMBI - Ajeng Cindy kinanthi; Mulyadi Mulyadi; Agus Lestari (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2026)
This research is motivated by the importance of cooperation between schools and the Business and Industrial Sector (DUDI) in improving vocational high school (SMK) graduates’ competencies to meet labor market demands through the Industrial Work Practice (PKL) program. This study aims to analyze the implementation of cooperation between schools and DUDI in improving graduate competencies at SMK Negeri 4 Jambi City through PKL activities. This research employed a qualitative approach with a case study design. Data were collected through interviews, observations, and documentation involving the Vice Principal for Public Relations, PKL supervising teachers, and students participating in the PKL program. Data analysis was conducted through data reduction, data display, and conclusion drawing, while data validity was tested using source and technique triangulation. The results show that the implementation of cooperation between the school and DUDI in the PKL program has been carried out effectively through good communication between schools and industry, the availability of supporting resources, positive implementer attitudes, and clear PKL implementation procedures. This cooperation contributes to improving students’ competencies in terms of knowledge, skills, and work attitudes.